Actualization of Pancasila as a Reflection of Young Leaders Role in Nurturing the Nation - Anggriawan, Kevlin; Ahmad, Endang; Nurgiansah, T Heru (CV. Rayyan Dwi Bharata, 2025)
Pancasila is a basic philosophy of the Indonesian nation that still exists today to answer personal problems that disrupt national stability. Speaking of the leadership of young figures, there needs to be a reflection that bridges in answering the needs of the nation and state at this time. Leadership that boils down to Pancasila will form a tough character of young figures in facing turbulent problems both from within and from outside. Pancasila will not be obsolete because Pancasila's determination is so strong that it is useful for young leaders in leading the nation and state in the future. This article uses a literature study method consisting of searching for articles from various sources that support theoretically through SAGE Journals, Google Scholar, and books that support to perfect the results of writing this article. The results of this study will describe holistically the leadership style of young figures based on Pancasila to look forward to a golden Indonesian future. The position of youth is very sacred in order to answer the challenges of the current digital era so that decadence does not occur due to complex changes in the times.